2012
DOI: 10.1007/s11906-012-0307-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Lipotoxicity in the Cardiovascular System

Abstract: Cardiovascular diseases account for approximately one third of all deaths globally. Obese and diabetic patients have a high likelihood of dying from complications associated with cardiovascular dysfunction. Obesity and diabetes increase circulating lipids that upon tissue uptake, may be stored as triglyceride, or may be metabolized in other pathways, leading to the generation of toxic intermediates. Excess lipid utilization or activation of signaling pathways by lipid metabolites may disrupt cellular homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 120 publications
2
67
0
1
Order By: Relevance
“…These observations are consistent with skeletal muscle studies in patients with type 2 diabetes, indicating a threefold higher lipid accumulation specifically at the sarcolemma that can be reduced by an exercise training intervention (24). Taken together, these results support the contention that a lipotoxicity-driven mechanism contributes to mitochondrial dysfunction in type 2 diabetic muscle, (31,36) particularly in the subsarcolemmal locale. With that being said, one must consider that the con- …”
Section: H61supporting
confidence: 87%
“…These observations are consistent with skeletal muscle studies in patients with type 2 diabetes, indicating a threefold higher lipid accumulation specifically at the sarcolemma that can be reduced by an exercise training intervention (24). Taken together, these results support the contention that a lipotoxicity-driven mechanism contributes to mitochondrial dysfunction in type 2 diabetic muscle, (31,36) particularly in the subsarcolemmal locale. With that being said, one must consider that the con- …”
Section: H61supporting
confidence: 87%
“…Recent studies have emphasized that oxidative stress and chronic inflammatory processes are important in the pathophysiology of obesity-related cardiovascular disorder [4]. Uncontrolled production of ROS and inflammatory cytokines induced by hyperlipidemia impairs cellular functions and causes cell apoptosis in a variety of tissues including the heart [28]. Therefore, elucidating the mechanism by which hyperlipidemia causes cardiac injury and discovering novel therapeutic agents are timely.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the fatty acid oxidation can be increased by daily AE in humans and rats [36,37]. Moreover, the increased fatty acid oxidation is benefit for reducing lipotoxicity and cardiovascular diseases risk in humans [38,39]. In addition, it was reported that AE had inhibition effect on the accumulation of TGrich lipoproteins in postmenopausal women [40], which may be caused by enhancing the affinity of TG-rich lipoproteins for lipoprotein lipase [41].…”
Section: Discussionmentioning
confidence: 99%